1975
DOI: 10.1139/m75-232
|View full text |Cite
|
Sign up to set email alerts
|

Bactericidal substance produced by Haemophilus influenzae b

Abstract: During bacteriophage studies on Haemophilus influenzer, it was observed that encapsulated type b and unencapsulated Rb strains released a bactericidal substance acitve against types a, c, d, e, and f H. influenzae, non-typable H. influenzae strains, other Haemophilus species, and certain members of the Enterobacteriaceae. The bactericidal activity was assayed by a plaque test utilizing an Rd strain as an indicator lawn and was also demonstrated in mixed broth cultures of a producer strain and an indicator stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
24
0

Year Published

1977
1977
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 9 publications
2
24
0
Order By: Relevance
“…We have reported that Haemophilus influenzae b produces a bactericidal factor that is active against Haemophilus species and certain members of the Enterobacteriaceae but not against gram-positive bacteria (13). Preliminary characterization of the bactericidal factor showed that it was a heat-stable protein of between 50,000 and 100,000 daltons in size, as determined by membrane filter retention.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…We have reported that Haemophilus influenzae b produces a bactericidal factor that is active against Haemophilus species and certain members of the Enterobacteriaceae but not against gram-positive bacteria (13). Preliminary characterization of the bactericidal factor showed that it was a heat-stable protein of between 50,000 and 100,000 daltons in size, as determined by membrane filter retention.…”
mentioning
confidence: 98%
“…Media. Brain heart infusion (BHI) agar and 3.7% BHI broth (Difco) were prepared and supplemented with hemin (Kodak) and nicotinamide adenine dinucleotide (NAD; Sigma) as previously described (sBHI) (13).…”
mentioning
confidence: 99%
“…influenzae, both encapsulated and nonencapsulated (LiPuma et al, 1990;Venezia & Robertson, 1975;Venezia et al, 1977). The exclusive production of H M C by type b encapsulated H .…”
Section: Introductionmentioning
confidence: 99%
“…Primer extension analysis revealed a putative transcriptional start site 34 bp upstream of the start codon, and the presence of a promoter immediately upstream of hmcI was confirmed by cloning the gene into a promoterless chloramphenicol acetyltransferase vector. To characterize the hmcI gene product, a His-HmcI fusion protein was constructed.Most type b-encapsulated strains of Haemophilus influenzae, including strains demonstrated to be genetically diverse by multilocus enzyme electrophoresis (22), produce the bacteriocin haemocin (HMC), which is toxic in vitro to virtually all non-type b strains of H. influenzae, both encapsulated and nonencapsulated (16,37,38). Data suggest that HMC exerts its toxicity by inhibiting DNA synthesis in susceptible strains (34); however, little is known about the genetic determinants conferring HMC production or immunity in H. influenzae.…”
mentioning
confidence: 99%
“…Most type b-encapsulated strains of Haemophilus influenzae, including strains demonstrated to be genetically diverse by multilocus enzyme electrophoresis (22), produce the bacteriocin haemocin (HMC), which is toxic in vitro to virtually all non-type b strains of H. influenzae, both encapsulated and nonencapsulated (16,37,38). Data suggest that HMC exerts its toxicity by inhibiting DNA synthesis in susceptible strains (34); however, little is known about the genetic determinants conferring HMC production or immunity in H. influenzae.…”
mentioning
confidence: 99%